2014
DOI: 10.9790/4861-06624751
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Solar Radiation Availability As It Affects Solar Panel Power Efficiency in Uyo and Port-Harcourt, Nigeria

Abstract: The effects of solar radiation on energy conversion efficiency of solar panel in Uyo and Port-Harcourt were investigated and the analysis compared. Solar radiation measurements as well as formal meteorological data were utilized. Data were also recorded from digital instruments used. Graphical analyses were made between solar radiation and current, voltage and efficiency. Results obtained show that solar radiation is directly proportional to current and efficiency but fairly stable with voltage. A comparative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
(1 reference statement)
1
1
0
Order By: Relevance
“…High humidity is followed by low temperature and lower solar radiation values [ Figures 5 and 6]. These results are in agreement with Ettah, et al [11] that increase in solar flux is observed when relative humidity is low. …”
Section: Humidity Evaporation and Solar Energysupporting
confidence: 89%
“…High humidity is followed by low temperature and lower solar radiation values [ Figures 5 and 6]. These results are in agreement with Ettah, et al [11] that increase in solar flux is observed when relative humidity is low. …”
Section: Humidity Evaporation and Solar Energysupporting
confidence: 89%
“…Again from the graph, the control panel has more output power than the dusty panel because of the accumulated dust on it. Hence high level of solar radiation leads to high power generation (Ettah et al, 2011) Figure Again from figure 5, increase in solar radiation favours increase in efficiency as seen in figure 5 above which inturns favours the over all output of PV module. The control panel has it all time efficiency to be 86% against 59% for the dusty panel.…”
Section: Figure 2 Output Power (W) Against Relative Humidity (%)mentioning
confidence: 84%
“…Efficiency (%) against Relative Humidity (%)Figure6a graph of efficiency against relative humidity. From the graph, continious increase in relative humidity leads to a decrease in efficiency and vise versa (Ettah et al, 2011).…”
mentioning
confidence: 98%
“…It is investigated the relationship between solar radiation and current, voltage and efficiency of solar panel. Solar radiation is evidently a determining factor when it comes to studying the natural potential of solar energy as a source of renewable energy (Ettah et al 2011). Which has analyzed the effects of component costs, FiTs (feed-in tariffs) and carbon taxes on grid-con-nected PV systems in Malaysian residential sector using the HOMER (Lau et al2016).…”
Section: Introductionmentioning
confidence: 99%